Analisis Ekonomi dan Sifat Mekanis Bambu Laminasi dalam Mendukung Desain Furnitur Ramah Lingkungan di Industri Furniture Yogyakarta - Iskandar Yasin; Dyah Ari Susanti; Emi Pratiwi (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
This research aims to analyze the utilization of laminated bamboo in terms of its economic aspects and mechanical properties to support the environmentally friendly furniture industry in the Yogyakarta region. The research method employed in this study is a literature review. The findings of the research indicate that the utilization of laminated bamboo as a material for the furniture industry can transform the local economy by encouraging innovation in the production of furniture and crafts made from laminated bamboo. As for the mechanical properties of laminated bamboo, several tests were conducted, including flexural strength, compressive strength, shear strength, tensile strength, and modulus of elasticity.